Managing economic volatility in Latin America - Gelos, Gaston; Werner, Alejandro M.; International Monetary Fund (Washington, D.C. International Monetary Fund, 2014)
How has Latin America coped with external shocks and economic vulnerabilities in the aftermath of the global financial crisis? Managing Economic Volatility in Latin America looks at how the region has fared in recent years in an environment of uncertainty. It presents a collection of novel contributions on capital flows, terms of trade, and macroeconomic policy in Latin America. The rigorous expert analysis offers an up-to-date guide to many of the key economic policy questions in the region. Chapters focus on important analytical issues, including assessing reserves adequacy and current account levels. The roles of macroeconomic policies and exchange rates regimes in coping with large capital inflows are examined, as well as the effectiveness of both monetary policy and fiscal policy in dealing with economic challenges in the region--Back cover.
Worrying about currency appreciation? : the missing link between Dutch disease and growth / Nicolâas Magud and Sebastiâan Sosa -- International reserve adequacy in Central America / Kristin Magnusson Bernard -- Estimating current account norms in Latin American emerging markets: a quantile regression approach / Roberto Perrelli -- Brazil's experience in managing capital inflows: the role of capital controls / Roberto Benelli, Alex Segura-Ubiergo, and W. Christopher Walker -- The impact of external developments on emerging market and developing economies: the role of exchange rate flexibility / Jorge Ivâan Canales-Kriljenko -- Public debt targeting: an application to Caribbean countries / Alejandro Guerson and Giovanni Melina -- What is driving financial dedollarization in Latin America? / Mercedes Garcâia-Escribano and Sebastiâan Sosa -- Interest rate and exchange rate channels in dollarized and non-dollarized economies / Santiago Acosta-Ormaechea and David Coble.
Includes bibliographical references and index.
Keywords: Capital movements -- Latin America; Foreign exchange reserves -- Latin America; Foreign exchange rates -- Latin America; Fiscal policy -- Latin America; Monetary policy -- Latin America